Determinants of antibiotic over-prescribing for upper respiratory tract infections in an emergency department with good primary care access: a quantitative analysis. (July 2021) - Huang, Z.; Weng, Y.; Ang, H.; Chow, A.
Summary: Background: Upper respiratory tract infections (URTI) account for the highest proportion of non-urgent visits to the emergency department (ED), resulting in unnecessary antibiotic use. Aim: This study sought to understand the determinants of antibiotic prescribing for URTI among 130 junior physicians in a busy adult ED in Singapore. Methods: Forty-four Likert-scale statements were developed with reference to a prior qualitative study, followed by an anonymous cross-sectional survey among ED junior physicians. Data analysis was performed with factor reduction and multivariable logistic regression. Findings: One-in-six (16.9%) physicians were high antibiotic prescribers (self-reported antibiotic prescribing rate of >30% of URTI patients). After adjusting for place of medical education and years of practice as a physician, perceived over-prescribing of antibiotics in the ED (adjusted odds ratio (OR) 2.37, 95% confidence interval (CI) (1.15, 4.86), P =0.019) and perceived compliance with the antibiotic prescribing practices in the ED (adjusted OR 2.10, 95% CI (1.02, 4.30), P =0.043) were positively associated with high antibiotic prescribing. In contrast, high antibiotic prescribers were 6.67 times (95% CI (1.67, 25.0), P =0.007) less likely to treat and manage patients with URTI symptomatically and 7.12 times (95% CI (1.28, 39.66), P =0.025) more likely to depend on diagnostic tests to prescribe antibiotics than the regular antibiotic prescribers. Conclusion: Organizational-related factors (organizational norms and culture) were strong determinants of antibiotic prescribing practices for uncomplicated URTI in the ED. Other contributing factors include diagnostic uncertainty and knowledge gaps. Role-modelling of institutional best practice norms and clinical decision support tools based on local epidemiology can optimize antibiotic prescribing in the ED.